2021
DOI: 10.1085/jgp.202012815
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathic troponin mutations predominantly occur at its interface with actin and tropomyosin

Abstract: Reversible Ca2+ binding to troponin is the primary on-off switch of the contractile apparatus of striated muscles, including the heart. Dominant missense mutations in human cardiac troponin genes are among the causes of hypertrophic cardiomyopathy (HCM) and dilated cardiomyopathy. Structural understanding of troponin action has recently advanced considerably via electron microscopy and molecular dynamics studies of the thin filament. As a result, it is now possible to examine cardiomyopathy-inducing troponin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
(103 reference statements)
0
21
0
Order By: Relevance
“…Numerous genetic studies revealed a large number of mutations in genes encoding troponin proteins (for example, by the type of substitution or deletion of one or several nucleotides), which led to the replacement of the corresponding amino acids and disruption of the regulatory function of troponins, phenotypically manifested in the form of various contractile dysfunctions and cardiomyopathies. [3][4][5][6][7][8] The etiopathogenesis and clinical manifestations of such disorders are described in sufficient detail in several review papers. [6][7][8] The amino acid composition of the two proteins included in the troponin complex (cTnI and cTnT) of the cardiac muscle differs from the amino acid composition of these proteins localized in the troponin complex of skeletal muscle, while the amino acid composition of cTnC and skeletal troponin C are completely identical.…”
Section: Important Aspects Of the Clinical Biochemistry Of Cardiac-specific Troponinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous genetic studies revealed a large number of mutations in genes encoding troponin proteins (for example, by the type of substitution or deletion of one or several nucleotides), which led to the replacement of the corresponding amino acids and disruption of the regulatory function of troponins, phenotypically manifested in the form of various contractile dysfunctions and cardiomyopathies. [3][4][5][6][7][8] The etiopathogenesis and clinical manifestations of such disorders are described in sufficient detail in several review papers. [6][7][8] The amino acid composition of the two proteins included in the troponin complex (cTnI and cTnT) of the cardiac muscle differs from the amino acid composition of these proteins localized in the troponin complex of skeletal muscle, while the amino acid composition of cTnC and skeletal troponin C are completely identical.…”
Section: Important Aspects Of the Clinical Biochemistry Of Cardiac-specific Troponinsmentioning
confidence: 99%
“…[3][4][5][6][7][8] The etiopathogenesis and clinical manifestations of such disorders are described in sufficient detail in several review papers. [6][7][8] The amino acid composition of the two proteins included in the troponin complex (cTnI and cTnT) of the cardiac muscle differs from the amino acid composition of these proteins localized in the troponin complex of skeletal muscle, while the amino acid composition of cTnC and skeletal troponin C are completely identical. 1,2,9 The main site of localization of cardiac-specific troponin proteins (cTnI, cTnT) is the myocardium, which allows their use as specific biomarkers for identification of cardiac muscle alteration.…”
Section: Important Aspects Of the Clinical Biochemistry Of Cardiac-specific Troponinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their analyses, they propose that developing effective treatments for these disorders will greatly benefit from binning patient subpopulations based on common underlying biophysical mechanisms that drive the molecular disease pathogenesis. Tobacman and Cammarato (2021) hone in on the locations of pathogenic and non-pathogenic troponin mutations in a thin filament atomic model. They show that the large majority of pathogenic sites are in troponin regions that inhibit contraction via direct contacts with actin or tropomyosin.…”
Section: Papersmentioning
confidence: 99%
“…To address the molecular component of this challenge, we have previously developed an atomistic model of the CTF that includes all protein components and regions. To our knowledge, this is the only full atomistic model and is critically important as one addresses mutations near “unstructured” regions not resolved in any previous experiment, where most variants arise ( 20 ). The full atomistic model has previously been used as a mechanistic probe to simulate structural and dynamic changes induced by mutations that are not addressable by experiment.…”
Section: Introductionmentioning
confidence: 99%